Amyloid deposition and brain structure as long-term predictors of MCI, dementia, and mortality. (22nd May 2018) - Lopez, Oscar L.; Becker, James T.; Chang, YueFang; Klunk, William E.; Mathis, Chester; Price, Julia; Aizenstein, Howard J.; Snitz, Beth; Cohen, Ann D.; DeKosky, Steven T.; Ikonomovic, Milos; Kamboh, M. Ilyas; et al.
Abstract : Objectives: To test the hypothesis that brain structural integrity (i.e., hippocampal [HIP] volume), white matter lesions (WMLs), and β-amyloid deposition are associated with long-term increased risk of incident dementia and mortality in 183 cognitively normal individuals and patients with mild cognitive impairment (MCI) aged 80 years and older. Methods: All participants had a brain structural MRI scan and PET scan with 11 C-labeled Pittsburgh compound B in 2009 and were reexamined yearly through 2015 (mean follow-up time 5.2 ± 1.3 years). Results: In the last evaluation through 2010–2015, 56 (31%) participants were cognitively normal, 67 (37%) had MCI, and 60 (33%) had dementia. Fifty-seven (31%) died during follow-up, and 20 (35%) developed dementia before their death. All 3 biomarkers were independent predictors of incident dementia in all participants. After adjusting for the risk of dying, amyloid deposition and WMLs remained strong predictors. Of the 60 participants with incident dementia, 54 (90%) had at least one imaging abnormality. Participants with no biomarker positivity had a very low risk of dementia (16%), while 75% of the participants with the 3 biomarkers progressed to dementia. HIP volume and β-amyloid deposition were associated with death only in participants with MCI. Conclusions: This study showed the presence of more than one biomarker was a stronger long-term predictor of incident dementia than any biomarker alone. After adjusting for the risk of dying, amyloid deposition and WMLs were stronger predictors of dementia than HIP volume. The risk of dying during follow-up was associated with both neurodegeneration and amyloid deposition, especially in individuals with MCI.